Inside Job: Exploring the Connection Between Whistleblowing and Perceptions of Procedural Justice. (2nd January 2020) - Exmeyer, Patrick C.
Abstract : Recent instances of whistleblowing by U.S. federal employees have reinvigorated scholarly interest in its role toward ethical administration. Previous studies have expanded our understanding of how factors such as organizational conditions; individual characteristics; motives; and perceived consequences shape decisions to engage in whistleblowing. However, studies examining employee perceptions of organizational fairness as a factor in disclosure processes remain absent from this literature. This study fuses whistleblowing and organizational justice by examining organizational, demographic, and legislative factors influencing employee perceptions of procedural justice. Findings from the study suggest that although the actions of external disclosure channels and enactment of federal whistleblower legislation have minimal impact on perceptions of procedural justice, employee supervisory status and organizational commitment are positively associated with elevated employee perceptions of procedural justice. Implications of the study and additional research dimensions are discussed.